Acculturation of Sundanese Culture in Padang City in 1969-2020 - Yenti, Yetri Ermi; Zulqaiyyim, Zulqaiyyim; Midawati, Midawati (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to determine the process of acculturation of customs, traditions, language, and culinary between Sundanese and Minangkabau tribes in Padang City. The research method used is the historical method through four stages, namely first, heuristics, namely the stage of collecting data in the form of documents or books, articles, journals and interviews. Second, source criticism is testing data by conducting internal and external criticism of data from various sources. Third, interpretation, which is the interpretation of data so that it becomes a meaningful fact. The last stage is historical writing in the form of a thesis. The results show that cultural acculturation includes aspects of language, traditions, food and clothing. This acculturation is supported by marriage between ethnicities, economic relations, similarities in beliefs and views of life resulting in unity. The unity is maintained by individual cultural agents (Sundanese cultural activists in Padang City and groups (Paguyuban Warga Sunda Sumatera Barat, local government, ethnic Minang). The cultural activists agreed to create peace in everyday life according to their respective roles and positions, so that Sundanese culture has social engineering that can build harmony in Padang City.